The cGAS-STING Pathway: A Promising Immunotherapy Target - Ou, Liang; Zhang, Ao; Cheng, Yuxing; Chen, Ying (Frontiers in Immunology, 2021)
With the continuous development of immunotherapy, researchers have paid more attention to the specific immune regulatory mechanisms of various immune responses in different diseases. As a novel and vital innate immune signal pathway, the cGAS-STING signal pathway activated by nucleic acid substances, interplays with other immune responses, by which it participates in regulating cancer, autoimmune and inflammatory diseases, microbial and parasitic infectious diseases, and other diseases. With the exception of its role in innate immunity, the growing list of researches demonstrated expanding roles of the cGAS-STING signal pathway in bridging the innate immunity (macrophage polarization) with the adaptive immunity (T lymphocytes differentiation). Macrophages and T lymphocytes are the most representative cells of innate immunity and adaptive immunity, respectively. Their polarization or differentiation are involved in the pathogenesis and progression of various diseases. Here we mainly summarized recent advanced discoveries of how the cGAS-STING signal pathway regulated macrophages polarization and T lymphocytes differentiation in various diseases and vaccine applications, providing a promising direction for the development and clinical application of immunotherapeutic strategies for related diseases.